Characterizing foulants on slotted liner and probing the surface interaction mechanisms in organic media with implication for an antifouling strategy in oil production. (15th April 2021) - Gong, Lu; Wang, Jingyi; Xiang, Li; Huang, Jun; Fattahpour, Vahidoddin; Roostaei, Morteza; Mamoudi, Mahdi; Fermaniuk, Brent; Luo, Jing-Li; Zeng, Hongbo
Graphical abstract: Highlights: Fouling phenomena have caused serious damages to oil and gas industries. Fine solids and asphaltenes are the major components of foulants. Both VDW attraction and steric repulsion contributes to surface interactions. Less foulants have been detected on electroless nickel-phosphorus coating. Abstract: Fouling phenomena are commonly observed in oil production processes, which have caused many challenging issues. Many previous studies focused on fouling in aqueous environment. However, the characterization of foulants and underlying interaction mechanism in organic media still remain limited, which is of fundamental and practical importance. In this work, the foulants on slotted liner samples were characterized, which have served in an oil wellbore based on steam-assisted gravity drainage (SAGD) operation for about six months. The foulants were demonstrated to be fine mineral solids (e.g., silica) and organic materials (e.g., asphaltenes). Atomic force microscope (AFM) colloidal probe technique was employed to quantify the interaction forces of silica particles or asphaltenes with carbon steel (L80) substrates with or without electroless nickel-phosphorus (EN) coating in organic media. The results demonstrated that the corrosion on L80 surface could significantly enhance the adhesion with silica particles and asphaltenes, aggravating the fouling phenomena; while the EN coating could effectively eliminate the corrosion and show good antifouling property. Quartz crystal microbalance with dissipation monitoring (QCM-D) technique was applied to investigate the dynamic adsorption behaviors of asphaltenes on iron (a major component of L80) and EN coating surfaces. The QCM-D results showed that much less asphaltenes were adsorbed on EN coating than that on iron, which agrees well with the force measurements. This work provides useful insights on the fouling processes and fundamental surface interaction mechanisms of fine solids, asphaltenes and substrates in oil, with implications on developing effective antifouling strategies (e.g., functional coatings) in oil production.